KOTA CILEGON IMPLEMENTASI PROGRAM PEMBERDAYAAN SOSIAL DALAM REHABILITAS RUMAH TIDAK LAYAK HUNI DI KOTA CILEGON - Kausar, Ronald Al; Yulianti, Rina; Stiawati, Titi (Jurnal Kebijakan Pembangunan Daerah, 2021)
Poverty alleviation is a concern and focus of the Cilegon Municipal Government as an effort to implement government functions in terms of service, empowerment and development to the community. Looking at the poverty rate in terms of the existence of uninhabitable homes in the City of Cilegon. Of course, the local government makes efforts to overcome it by issuing a policy contained in the form of a program. The theory used in this study is the implementation of policies put forward by Hill and Hupe which consists of three aspects of managing policy implementation, namely managing policy processes, managing relationships between organizations and managing internal and external relationships. The research method used is a descriptive method with a qualitative approach. Determination of informants using purposive techniques. Based on the results of research, the rehabilitation program of uninhabitable houses in the city of Cilegon has not fully run optimally in the level of realization of development work. Assistance programs aimed at the poor by providing financial assistance in the form of self-help stimulants, where the community is required to build independently based on community or government initiatives with a community empowerment based approach, so that the realization of community hope and welfare.